Estratigrafia e evolução estrutural do segmento setentrional da faixa de desdobramentos Paraguai - Araguaia - ABREU, Francisco de Assis Matos de (Universidade Federal do Pará, 2017)
The northern part of the Paraguai-Araguaia orogenic belt comprises a significant portion of the South American Platform. Here, the Brazilian geotectonic cycle (550-900 m.y), produced a mountain chain through a complex sequence of sedimentary metamorphic, magmatic, and structural events along the eastern margin of the Amazon craton. The lithologic sequence is designated stratigraphically as the Baixo Araguaia Supergroup which comprises the Estrondo Group and the overlying Tocantins Group. The basal formation in the Estrondo Group is the Morro do Campo Formation which consists of quartzites and subordinate schists and gneisses. The Xambioá overlies the Morro do Campo and includes several kinds of schists. The Tocantins Group is formed by Couto Magalhães Formation, represented by phyllites and intercalated quartzites and the overlying Pequizeiro Formation consiwts of pelitic sediments and Mg-rich igneous derivatives. The Estrondo and the Tocantins groups are intruded by ultramafic, mafic, and granitic rocks that are associated with late and post-tectonic igneous events. The Rio das Barreiras Formation, a sedimentary sequence represented by a polymictic conglomerate with carbonate matrix and sandy and silty interlayers, unconformably overlies the Pequizeiro Formation and may represent erosional remnants of a final phase of the Brazilian cycle. Primary lithologic structures in Baixo Araguaia Su pergroup are preserved as relict compositional stratification, inclined, parallel, and graded bedding in metasediments, and flow structures in the igneous rocks. Superposed penetrative planar and linear deformation structures are present in several generations. The regional N-S striking schistosity is of axial-plane type and is related to the intrafolial folds, with an easterly dip getting vergence to Amazon craton. The regional dip is 309 and decreases to abaut 159 adjacent to the Amazon craton. Gneissic banding parallels schistosity of overlying schists in the larger folds and they share a common mineral lineation. Polyphase deformation is recorded by a fold sequence which varies in scale from 1 cm to 30 km and is related to the differents structural levels within the crust. The lower structural level includes: a) similar-type intrafolial isoclinal folds which are contemporaneous with regional metamorphism; b) similar tight folds which involve the s.chistosity and transposed bedding; c) shear folds of crenulation developed near to the top of the level in the more plastic horizons. The intermediate level comprises; d) isolated regional flexures near the localities of Colméia, Xambioà-, Lontra, Muricizal; e) two generations of open and cross folds associated with the Iriri-Martírios lineament zone. N-S and NW-SE fracture and fault systems cut ali stratigraphi.c units of the Baixo Araguaia Supergroup. The faults consist of: 1) NW treding transcurrent fault with strike iengths of severa]. Kilometers; 2) thrust faults with N-S- strike such as those near Andorinhas and Muricizal mountains; 3) N-S striking normal faults developed at the edge of the Parnaíba basin and elsewhere. The mapped facies sequence ranges from incipient greenschist facies in the west to amphibolite facies in the east implying an Bastward increase in metamorphic grade. Sericite to garnet isograds are discernibles. Three magmatic events are distinguished. They comprises: a) pre-tectonic basic and ultrabasic plutonic-volcanic magmatism; b) late-tectonic granitic intrusion; c) post- tectonic unfoliated granitic intrusions. Eleven K-Ar mica dates from gneisses and schists of the orogenic belt yield values in the range of 516 ± 10 m.y to 358 ± 19 m.y. (Brazilian Cycle). Five Rb/Sr determinations from the gneissic core of the Colméia fold gives values around 2,000 m.y (Amazonic cycle). The geologic evolution of the northern Paraguai-Araguaia orogenic belt consists of three sequential stages: I) deposition of psammitic and pelitic sediments comprising the Estrondo and lower Tocantins Groups. Basic and ultrabasic igneous activity in late Tocantins time result in the deposition of mixture of pelitic sediments and Mg-rich igneous material which comprise the Pequizeiro Formation. II) polyphase deformation, metamorphism, magmatism, and orogenic uplift followed. These events are subdivided as follows: 1) F1 - deformation and regional metamorphism (Ma) in which So (original bedding) was transposed by isoclinal folding to S1 (regional schistosity) and progressive metamorphism produced sericite and garnet map zunes; 2) F2 - deformation produced tight folds in the schistosity (S1) resulting an axial plane surface (S2); well-marked mineral lineation (L2); 3) F3 deformation developed crenulation folds and a second phase of transposition (S3); e) F4 - deformation produced large folds accopanied by migmatization and late-tectonic granitic intrusions; 5) F5 - deformation formed small-scale plastic folds in cataclastic zones along the Iriri-Martírios lineament. III) The post-metamorphic Rio das Barreiras Formation was then deposited unconformably over this structural sequente and the final deformation event produced fault movements (transcurrent, thrust and normal), established joints, and permitted the rise of post-tectonic granitic plutons. This stage marks a transition from an environment of compressional stress to one of tensional stress on the regional scale. Subsequent to stageIII, consolidation of the South American platform occurred. Related erosional, sedimentary, magmatic, and'tectonic processes affedted this ares at numerous times throughout post-Brazilian cycle time.